Comparative analysis between the basic unit cost of single-family residences calculated for the municipality of Juazeiro do Norte and the one published by Sinduscon for the state of Ceará - Fonseca, Ramon Ytalo Leandro da; Tavares, Thayná Cavalcante (Brazilian Journal of Production Engineering, 2024)
The Basic Unit Cost (CUB) is a fundamental tool in civil construction, widely used to make initial cost estimates for different types of projects and to monitor how these costs vary over time. Created by Federal Law 4,591/64, the CUB is published monthly by state construction unions, serving as an important reference point for each state. However, differences in material and service prices between municipalities can affect the accuracy of this indicator. This study aimed to calculate the specific CUB of Juazeiro do Norte-CE, according to the guidelines of NBR 12.721:2006, and compare it with the state CUB published by SINDUSCON-CE. By analyzing the data from August 2023, notable differences were identified: while labor costs in Ceará are higher than in Juazeiro do Norte, materials are more expensive in Juazeiro do Norte than in the rest of the state. These variations suggest that the state CUB does not accurately reflect the specific construction costs of Juazeiro do Norte, highlighting the need for adjustments so that the state indicator is more aligned with local conditions.
Keywords: Basic unit cost; ABNT NBR 12.721:2006; Juazeiro do Norte-CE